Carbon Estimation Of Rhizophora apiculata Stand and Soil Organik Carbon In Mangrove Ecosystem Cawan Island, Indragiri Hilir, Riau - Khairul Mukmin Lubis; Aras Mulyadi Mulyadi; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTRhizophora apiculata the dominant mangrove vegatation species growing in Cawan Island, Indragiri Hilir regency, Riau. R. apiculata as one of the spesies in mangrove has considerable CO2 inhibition potential. Beside estimating carbon in R.apiculata standing, soil organic carbon was also analyzed conducted at different depths. This research was conducted in September-November 2017, used survey method, analysis of biomass using allometric, the size of the stand diameter as independent variable obtained by non destructive sampling, carbon estimation and assessment CO2 refer BSN (2011). Soil organic carbon was analyzed with Los On Ignation method in Marine Chemical Laboratory Fishries and Marine Faculty, University of Riau. Average biomass, carbon content, CO2 R. apiculata uptake were 45,51 ton / ha, 21,39 ton C / ha, 78,43 ton CO2 / ha, respectively. The average distribution of soil organic carbon deposits at depths of 0cm - 15cm, 15cm - 30cm, 30cm - 50cm, 50cm - 100cm and> 100cm respectively were 275.63 ton C / ha, 275.83 ton C / ha, 277 , 29 ton C / ha, 562.90 ton C / ha and 271.95 ton C / ha. In each soil layer, the depth of 50cm - 100cm larger. R. apiculata standing carbon and soil organic carbon have positive regression result with linear regression equation y = 1,2759x - 2101,2 with terminated value (R2) equal to 0,1569 and value (r) with the same value 0,40 then the soil carbon carbon deposits with standing carbon deposits have substantial relationships. Keywords: Mangrove, Soil, Biomass, Carbon